2005
DOI: 10.1111/j.1572-0241.2005.41700.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Influences in Irritable Bowel Syndrome: A Twin Study

Abstract: Genetic factors are of little or no influence on IBS where the predominant influences appear to be environmental.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
2
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 20 publications
0
60
2
5
Order By: Relevance
“…The schizophrenia literature illustrates the usefulness of endophenotypes in genetic analyses of mental disorders (11) and in understanding these disorders at the cellular and molecular levels (2). As with those mental disorders, there is evidence from familial clustering and twin studies to support a heritable component in IBS (26), although this is somewhat controversial (31). Although our laboratory focuses predominantly on peripheral organ functions, investigation of genetic influences on brain structure or functions in the development of IBS using neuroimaging may provide further advances in understanding, as in schizophrenia (2).…”
Section: Discussionmentioning
confidence: 99%
“…The schizophrenia literature illustrates the usefulness of endophenotypes in genetic analyses of mental disorders (11) and in understanding these disorders at the cellular and molecular levels (2). As with those mental disorders, there is evidence from familial clustering and twin studies to support a heritable component in IBS (26), although this is somewhat controversial (31). Although our laboratory focuses predominantly on peripheral organ functions, investigation of genetic influences on brain structure or functions in the development of IBS using neuroimaging may provide further advances in understanding, as in schizophrenia (2).…”
Section: Discussionmentioning
confidence: 99%
“…Because monozygotic twins share the exact same genetic code and dizygotic twins share half of the same genetic code, comparing concordance rates between monozygotic and dizygotic twins allows the opportunity to quantitate the contributions that genetics and environment each make to the development of the disease. Five twin studies demonstrate that the genetic contribution to IBS appears to range between 0 and 20% (8)(9)(10)(11)(12). The reasons for the heterogeneity in genetic liability estimates are not clear; they may represent true population-based differences, but are likely the result of methodological differences with respect to how IBS status was defined and how the information was collected.…”
Section: What Evidence Is There For An Ibs Gene?mentioning
confidence: 99%
“…Regression analysis showed that the presence of IBS in the respondent's parents made a larger contribution to the risk of having IBS than did the presence of IBS in one's twin [24] , and a study with a United Kingdom twin database provided confirmation of the influence of social learning over heredity in the development of IBS [25] .…”
Section: Childhood Social Learning Effects On Childhood Illness Behaviormentioning
confidence: 91%